Priscilla Layne. White Rebels in Black: German Appropriation of Black Popular Culture. U of Michigan P, 2018. - Mona Eikel-Pohen (Studies in 20th & 21st Century Literature, 2021)
Review of Priscilla Layne. White Rebels in Black: German Appropriation of Black Popular Culture. U of Michigan P, 2018. ix + 259 pp.
Keywords: Black popular culture; German studies; literature; film